2012
DOI: 10.1097/qai.0b013e31823fd215
|View full text |Cite
|
Sign up to set email alerts
|

CCR5 Expression Is Elevated on Endocervical CD4+ T Cells in Healthy Postmenopausal Women

Abstract: Background New HIV-1 infections are increasing in older American women largely through heterosexual transmission. Activated CD4+ T-cells and CCR5 expression are linked to HIV-1 susceptibility, but whether these parameters are altered in the cervix of older women is unknown. Methods Whole blood and in some instances endocervical brush samples were collected from healthy premenopausal (n=22) and postmenopausal women (n=24). Percentages of HLA-DR(DR)+CD38(38)+CD4+ T-cells, and HIV-1 chemokine coreceptor express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 44 publications
1
37
0
Order By: Relevance
“…[34,35]. It is possible that we did not observe this as we focused on the soluble immune mediators rather than the cellular components in the genital tract.…”
Section: Changes In Anti-hiv Activity In Cvlmentioning
confidence: 64%
“…[34,35]. It is possible that we did not observe this as we focused on the soluble immune mediators rather than the cellular components in the genital tract.…”
Section: Changes In Anti-hiv Activity In Cvlmentioning
confidence: 64%
“…42 Increased CCR5 expression on endocervical CD4 + T cells was also reported in healthy post-menopausal women. 43 These data collectively suggest that increased expression of CCR5 may contribute to the epidemiological link between DMPA and HIV, but larger studies are needed to address the impact of HC on the number and function of mucosal and systemic immune cell populations.…”
Section: Potential Mechanismsmentioning
confidence: 91%
“…Additionally, CCR5 expression may be regulated by the menopausal status, since cells from postmenopausal women expressed more CCR5 than premenopausal women 70 (Rodriguez-Garcia et al, unpublished data). Saba et al 15 found that about 50% of CD4 + T cells expressed HIV-coreceptor CCR5.…”
Section: Effect Of the Tissue Environment On Immune Cellsmentioning
confidence: 99%